A Discussion of Scientific Methods for Setting Manufacturing Tolerances - Weiss, Paul R. (My University, 1993)
Several traditional and newer techniques for setting manufacturing tolerances are discussed. The traditional methods include worst case, statistical case, and proportional and constant factor scaling. Newer methods, such as Optimization and Monte Carlo Simulation are described more briefly. The Estimated Mean Shift model is included as a method for setting tolerances more realistically, while at the same time improving the communication between design and manufacturing departments. Additionally, some techniques are described for setting initial tolerances when little or no data or tables are available. Three tolerancing examples are included.